A novel and sensitive agar plug assay for screening of asparaginase-producing endophytic fungi from Aegle marmelos - Patil, Mohini P.; Patil, Ravindra H.; Maheshwari, Vijay Laxminarayan (Acta Biologica Szegediensis, 2012)
Twelve strains of asparaginase (L-asparagine amidohydrolase, E.C. 3.5.1.1) producing filamentous fungi were isolated from the bark and leaves of Aegle marmelos Linn. In the present study, a new method of isolation and selective screening of asparaginase producing endophytic fungi was developed. Asparaginases producing filamentous fungi were screened by a novel rapid dye based agar plug assay. Agar plug screen is a novel method for efficient screening of large number of fungal isolates. All endophytic fungi could grow on modified Czapek Dox agar medium with phenol red, a dye indicator that changes from yellow (acidic condition) to pink (alkaline condition). This method is not only rapid and cost effective but also less labor intensive and could be efficiently used for isolating high yielding strains.